2016
DOI: 10.1080/15548627.2016.1203500
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling ofLeishmania donovani-infected host cells uncovers the regulatory role of MIR30A-3p in host autophagy

Abstract: Leishmania is an obligate intracellular parasite that replicates inside phagolysosomes or parasitophorous vacuoles (PV) of the monocyte/macrophage lineage. It reprograms macrophages and produces a metabolic state conducive to successful infection and multiplication. MicroRNAs (miRNAs), a class of small 22 to 24 nucleotide noncoding regulatory RNAs alter the gene expression and consequently proteome output by targeting mRNAs, may play a regulatory role in modulating host cell functions. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 55 publications
0
47
0
1
Order By: Relevance
“…To best of our knowledge, the ability of L. donovani to actively inhibit classical mTOR regulated autophagy, at early stages of infection is a novel strategy that promotes pathogen survival (Figs 2 & 3, Supplementary Fig 3). Nevertheless, recent reports and the present findings make it clear that leishmania do activate autophagic machinery in host cells, albeit with delayed kinetics (Fig 1) in the case of L. donovani (13,18). In respect to the latter, it was of interest to establish whether delayed autophagy involves mTOR-dependent cell signaling or an alternate signaling pathway which is mTOR-independent.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…To best of our knowledge, the ability of L. donovani to actively inhibit classical mTOR regulated autophagy, at early stages of infection is a novel strategy that promotes pathogen survival (Figs 2 & 3, Supplementary Fig 3). Nevertheless, recent reports and the present findings make it clear that leishmania do activate autophagic machinery in host cells, albeit with delayed kinetics (Fig 1) in the case of L. donovani (13,18). In respect to the latter, it was of interest to establish whether delayed autophagy involves mTOR-dependent cell signaling or an alternate signaling pathway which is mTOR-independent.…”
Section: Discussionmentioning
confidence: 97%
“…Several species of leishmania have been observed to induce host autophagy, but the molecular mechanism(s) involved in the autophagy response have only recently begun to emerge (12)(13)(14)(15)(16)(17)(18)(19). For example, two recent studies reported a link between leishmania induced autophagy and a differentially expressed set of host micro RNAs (miRNAs), including MIR-30A-3p in infected cells (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations